1996
DOI: 10.1007/s002689900169
|View full text |Cite
|
Sign up to set email alerts
|

Hemostatic Methods for the Management of Spleen and Liver Injuries

Abstract: The spleen and liver are the most frequently injured organs during blunt and penetrating abdominal trauma. Emergency laparotomy is crucial for early control of bleeding and to prevent "secondary" injury as a result of physiologic splanchnic vasoconstriction and free oxygen radicals. Altogether 98 patients with spleen and liver injuries were treated over an 8-year period. Primary orthotopic spleen preservation could be achieved in 46 of 63 patients. In 58 patients with hepatic trauma, hemostatic treatment was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 13 publications
0
35
0
1
Order By: Relevance
“…Fibrin glue, which mimics the final stage in the coagulation cascade, is currently the most widely used hemostatic agent in liver surgery [6-8], and many studies showed its efficacy on hemostasis, biocompatibility, and biodegradability [9-11]. Therefore, we compared the properties of MAR with those of fibrin glue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fibrin glue, which mimics the final stage in the coagulation cascade, is currently the most widely used hemostatic agent in liver surgery [6-8], and many studies showed its efficacy on hemostasis, biocompatibility, and biodegradability [9-11]. Therefore, we compared the properties of MAR with those of fibrin glue.…”
Section: Discussionmentioning
confidence: 99%
“…Although several topical hemostatic agents have been developed and used in various surgical disciplines [5], fibrin glue is currently the most widely used in liver surgery [6-8]. This is because fibrin glue has been proved to have a hemostatic effect, biocompatibility, and biodegradability in many studies [9-11].…”
Section: Introductionmentioning
confidence: 99%
“…The surgical procedure used for the control of the bleeding can be chosen between: selective individual control of the bleeding vessels, compression of injure, mass ligature of the injured parenchymal tissue, partial resection of the organ, coagulation with electric scalpel, haemostatic sponges or application of topic haemostatic agents (collagen, gelatin or cellulose) 1,2,3 . One non-surgical alternative is the procedure involving the transfusion of haemoderivates 1,3 .…”
Section: Introductionmentioning
confidence: 99%
“…The best approach in these cases is splenorrhaphy with an absorbable mesh. An appropriately sized piece of Vicryl mesh with an absorbable thread is wrapped around the spleen, and the thread is pulled together on the hilar face to produce hemostasis without compromising intraparenchymal circulation [26]. It is extremely important that the pouch be slightly smaller than the spleen itself, so that the thread lies on the margin when it has been pulled taut.…”
Section: Mesh Splenorrhaphymentioning
confidence: 99%